Agriculture in Jamaica: Collection of papers of the IICA office in Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
Anexo No 7: 282 páginas